2007
DOI: 10.1177/117739280700200020
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Human Immunodeficiency Virus Type 1 Assembly, Maturation and Budding

Abstract: The targets for licensed drugs used for the treatment of human immunodeficiency virus type 1 (HIV-1) are confined to the viral reverse transcriptase (RT), protease (PR), and the gp41 transmembrane protein (TM). While currently approved drugs are effective in controlling HIV-1 infections, new drug targets and agents are needed due to the eventual emergence of drug resistant strains and drug toxicity. Our increased understanding of the virus life-cycle and how the virus interacts with the host cell has unveiled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 230 publications
(249 reference statements)
0
6
0
Order By: Relevance
“…Both release and infectivity are decreased for HIV particles containing excess GagPol, and these decreases are at least partially due to premature PR activation (45,46). This activation may result from dimerization of HIV-1 reverse transcriptase (RT), which, when it occurs in the context of Gag-Pol, can activate PR and have negative effects on budding and maturation (50). In contrast, MoMLV RT is monomeric, at least in solution (51), and thus, MoMLV RT likely cannot contribute to Gag-Pol-Gag-Pol dimerization and premature PR activation to the extent that HIV-1 RT can.…”
Section: Discussionmentioning
confidence: 99%
“…Both release and infectivity are decreased for HIV particles containing excess GagPol, and these decreases are at least partially due to premature PR activation (45,46). This activation may result from dimerization of HIV-1 reverse transcriptase (RT), which, when it occurs in the context of Gag-Pol, can activate PR and have negative effects on budding and maturation (50). In contrast, MoMLV RT is monomeric, at least in solution (51), and thus, MoMLV RT likely cannot contribute to Gag-Pol-Gag-Pol dimerization and premature PR activation to the extent that HIV-1 RT can.…”
Section: Discussionmentioning
confidence: 99%
“…The myristoylation of Gag is generally considered as essential for targeting the protein to the host plasma membrane (Morikawa et al, 1996). Dominant-negative mutations that directly interfere with Gag myristoylation, or indel mutations that block translation from the physiological start site or that create a loss-of-function gag transcript will perturb proper viral particle assembly at the plasma membrane, and hence block retroviral particle budding (Morikawa et al, 1996;Wapling, Srivastava, Shehu-Xhilaga, & Tachedjian, 2007). In addition to Myr, the conserved proline-rich PPxY motif also contributes to retrovirus budding, likely by interacting with the ESCRT machinery (Henzy, Gifford, Johnson, & Coffin, 2014), and its mutation strongly inhibits viral particle release (Segura-Morales et al, 2005).…”
Section: Targeting Group 1 Erv Sequences By Crispr-cas9 Genome Editingmentioning
confidence: 99%
“…Genetic studies have demonstrated that mutations in the Pol region of Gag-Pol, comprising protease (PR), reverse transcriptase (RT), and integrase (IN), can lead to defects in particle morphology, virion release, uncoating, reverse transcription, or nuclear localization of the preintegration complex ( 6 13 ). The mechanism by which the Pol region within Gag-Pol influences these events is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…How IN or Pol mutations could influence assembly has not been elucidated. There are several hypotheses, one of which is that mutations in IN or Pol interfere with Gag and Gag-Pol oligomerization, thereby disrupting the assembly process ( 11 , 13 ). Another hypothesis is that defects in IN may lead to premature protease action within the cells, and it has been shown that the inhibition of protease catalytic activity overcomes the assembly defects mediated by at least some of the IN mutants ( 12 ).…”
Section: Introductionmentioning
confidence: 99%